Sugarcane seed composition and changes during artificial ageing - Siqueira, G. F. [UNESP]; Pierre, J. S.; El Tahchy, A.; Glassop, D.; Singh, S.; Bonnett, G. D.; Rae, A. L. (CSIRO Publishing, 2015)
Sugarcane (Poaceae) has not undergone any commercial selection based upon seed characteristics. As the plant is grown from vegetative cuttings and the stalk harvested for its sucrose content, relatively little is known about its seed compared with other grass crops. The seeds of sugarcane were small, 1.8×0.8mm, and the embryo comprised about one-third of the seed volume. Among the samples analysed, the seed contained on average 37%, 20% and 10% of the fresh weight as starch, protein and lipid, respectively. Histochemical staining showed that the starch was confined to the endosperm and the lipid to the embryo and aleurone layer. Protein was found in the embryo, endosperm and aleurone layer. There were small but significant differences between the sources of sugarcane seed. The wild relative S. spontaneum had significantly less starch than the commercial hybrid sugarcane seed. The lipid content was higher for sugarcane seed than for the seeds of many other grasses, possibly because of the high ratio of lipid-containing embryo to endosperm. Following artificial ageing, the observed decline in seed viability was not closely reflected by any significant changes in composition, although protein and sugars were reduced after 168h. These results contribute to our understanding of the sexual reproductive biology of sugarcane, which is important for the science-based environmental risk evaluation of the release of genetically modified sugarcane.
Keywords: caryopsis; Saccharum